2012
DOI: 10.1007/s00601-012-0510-3
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Analytical Solutions of Dirac Equation with Spin and Pseudo Spin Symmetries for the Diatomic Molecular Potentials Plus a Tensor Term with Any Angular Momentum

Abstract: Approximate analytical solutions of the Dirac equation are obtained for some diatomic molecular potentials plus a tensor interaction with spin and pseudospin symmetries with any angular momentum. We find the energy eigenvalue equations in the closed form and the spinor wave functions by using an algebraic method. We also perform numerical calculations for the Pöschl-Teller potential to show the effect of the tensor interaction. Our results are consistent with ones obtained before.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…It is shown that in general the single-particle energies increase with ω 2 , as ω 2 2 appears in the right hand side of Eq. (104). More importantly, the pseudospin-up states with j > =l + 1/2 increase faster than the pseudospindown states j < =l − 1/2.…”
Section: Linear Tensor Potentialmentioning
confidence: 93%
See 2 more Smart Citations
“…It is shown that in general the single-particle energies increase with ω 2 , as ω 2 2 appears in the right hand side of Eq. (104). More importantly, the pseudospin-up states with j > =l + 1/2 increase faster than the pseudospindown states j < =l − 1/2.…”
Section: Linear Tensor Potentialmentioning
confidence: 93%
“…For the spherical case, extensive investigations have been made for the spherical harmonic oscillator [88][89][90]92,95,96], anharmonic oscillator [97], Coulomb [76,[99][100][101], Deng-Fan [102], diatomic molecular [103,104], Eckart [105,106], Hellmann [107], Hulthén [108][109][110][111], Manning-Rosen [112][113][114], Mie-type [115][116][117], Morse [118][119][120][121][122][123], Pöschl-Teller [124][125][126][127][128][129][130][131][132][133], Rosen-Morse [134][135][136][137], Tietz-Hua [138], Woods-Saxon …”
Section: Analytical Solutions At Pss Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting algebra of this contraction is a standard real Hopf algebra and depends on a dimension-full parameter κ instead of q. Since then, the algebraic structure of the κ -deformed Poincaré algebra has been investigated intensively and have become a theoretical field of increasing interest [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Through the field equations from the κ-Poincaré algebra (κ-Dirac equation [22][23][24]), we can study the physical implications of the quantum deformation parameter κ in relativistic and nonrelativistic quantum systems.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33]). Some studies have been developed taking into account the spin and pseudospin symmetry limits to study relativistic dynamics of physical systems interacting with a class of potentials [34][35][36][37][38][39][40][41]. The present work is proposed to investigate the κdeformed Dirac equation derived in Refs.…”
Section: Introductionmentioning
confidence: 99%